Functional outcomes and quality of life following free fibula flap harvest: a comparative analysis of flexor hallucis longus resection versus preservation - Zhao, Guanghui; Zhang, Xu; Du, Wei; Yuan, Junhui; Fang, Qigen (Frontiers in Oncology, 2025)
BackgroundThe free fibula flap (FFF) is a gold standard for maxillofacial reconstruction, yet debate persists regarding the functional impact of flexor hallucis longus (FHL) resection. This study evaluates donor-site morbidity and quality of life (QoL) following FFF reconstruction, comparing outcomes with and without FHL resection.MethodsA retrospective analysis of prospectively collected data was conducted for 93 patients undergoing FFF reconstruction. Patients were stratified into FHL-harvested and non-FHL groups. Primary outcomes included QoL, AOFAS scores, hallux flexion strength, range of motion (ROM), isokinetic dynamometry, and gait analysis. Assessments were performed preoperatively and at 3- and 6-month intervals.ResultsThe study cohort comprised 93 patients, with FHL harvested in 43 cases. The FHL group exhibited transient declines in QoL at 3 months, with partial recovery by 6 months. Both groups showed similar AOFAS score trajectories, with temporary declines at 3 months and near-complete recovery by 6 months. Hallux flexion strength decreased comparably in both groups at 3 months (FHL: −38%; non-FHL: −34%), with residual 18–20% deficits at 6 months. Isokinetic testing revealed transient plantar flexion weakness in the FHL group at higher velocities (90°/s: 54.2 ± 7.0 Nm vs. 58.6 ± 7.5 Nm pre-op, p=0.008), resolving by 6 months. Gait analysis demonstrated initial impairments in stride length and ankle ROM in the FHL group, normalizing by 6 months.ConclusionFHL resection during FFF harvest leads to transient functional and QoL impairments, but most deficits resolve within 6 months. Preservation is advisable when feasible, though FHL harvest remains safe for cases requiring additional soft tissue.